Anti-inflammatory activity of dominant compound of mahkota dewa fruit Phaleria macrocarpa Scheff. Boerl - Mariani, Ria; Wirasutisna, Komar Ruslan; Nawawi, As’ari; Adnyana, I Ketut (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
The anti-inflammatory effectof dominant compound of mahkota dewa fruit (Phaleria macrocarpaScheff. Boerl), a hydroxyl benzophenon glucoside,to Wistar female rats (using λ-karagenan as inflammatory inducer) has been investigated. The inflammation was measured by pletismometer. The test has been used physiology NaCl solution as a control andNaproxen at a dose of 22.5 mg/kg body weight as a standard. Anti-inflammatorytest was showed that the decreased inflammation of the isolate at a dose of 22.5 mg/kg body has twice lower than the standard.Key words: Phaleria macrocarpa, anti-inflammatory activity, hydroxyl benzophenon glucoside